Pengaruh Pengembangan Karir, Lingkungan Kerja dan Self Efficacy terhadap Komitmen Organisasi dengan Kepuasan Kerja sebagai Variabel Intervening pada Bank Riau Kepri Syariah di Kota Batam - Naufal, Muhammad Ade; Wibisono, Chablullah; Indrawan, Mohamad Gita; Indrayani, Indrayani; Ngaliman, Ngaliman (Universitas Batanghari Jambi, 2025)
The aim of this research is to determine and analyze the influence of career development, work environment and self-efficacy on organizational commitment with job satisfaction as an intervening variable at Bank Riau Kepri Syariah in Batam City. Data were collected using a questionnaire and distributed to 142 respondents. Statistical data analysis uses SEM-PLS (structural equation modeling partial least squares) and uses path analysis to test relationship patterns that reveal the influence of variables on other variables, both direct and indirect. The research results show that career development directly has a positive and significant effect on organizational commitment, but not significantly on job satisfaction. The work environment directly has a positive and significant effect on job satisfaction, but not significantly on organizational commitment. Self-efficacy directly has a positive and significant effect on job satisfaction and organizational commitment. Job satisfaction directly has a positive and significant effect on organizational commitment, but does not mediate the effect of career development on organizational commitment. Job satisfaction mediates the influence of the work environment and self-efficacy on organizational commitment.